1987
DOI: 10.1111/j.1399-6576.1987.tb02638.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ipratropium bromide aerosol on respiratory function in patients under ventilator treatment

Abstract: Twenty patients, 36-78 years old, with a history of chronic obstructive lung disease, and immediately after operation mostly for cardiac disease, were treated with ipratropium bromide (IB, 15 cases) or placebo (5 cases). A metered dose inhaler with a new adapter was used during postoperative ventilator treatment. In the IB group the heart rate did not change, but the inspiratory resistance decreased and the arterial oxygen tension increased. This is considered to indicate an effect not only on large but also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In contrast, the efficacy of aerosol delivery with an MDI in mechanically ventilated patients has had a checkered history. Early studies showed promising results (40,(44)(45)(46). In subsequent studies, different dosages of bronchodilators and different techniques of administration were used to evaluate the efficacy of MDIs in mechanically ventilated patients, leading to variable and often contradictory results (Table 1).…”
Section: Efficacy Of Bronchodilators In Mechanically Ventilated Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the efficacy of aerosol delivery with an MDI in mechanically ventilated patients has had a checkered history. Early studies showed promising results (40,(44)(45)(46). In subsequent studies, different dosages of bronchodilators and different techniques of administration were used to evaluate the efficacy of MDIs in mechanically ventilated patients, leading to variable and often contradictory results (Table 1).…”
Section: Efficacy Of Bronchodilators In Mechanically Ventilated Patientsmentioning
confidence: 98%
“…Both inhaled beta-adrenergic (2, 4-6, 48, 55) and anticholinergic bronchodilators (40,42) are effective in mechanically ventilated patients. Among the sympathomimetic drugs, inhaled isoproterenol hydrochloride (44,45), isoetharine mesylate (46), metaproterenol sulfate (48), fenoterol (41), and albuterol (2, 4-6, 42, 55) all produce significant bronchodilation.…”
Section: Choice Of Inhaled Bronchodilatormentioning
confidence: 99%
“…The goals of bronchodilator therapy are to reverse bronchoconstriction, decrease the work of breathing, and/or relieve dyspnea. Administration of either aerosolized b-adrenergic (26,29,(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93) or anticholinergic drugs (77,79,83,86) produces significant bronchodilator responses in ventilated patients. The combination of fenoterol and ipratropium bromide was found more effective than ipratropium alone in ventilated patients with COPD.…”
Section: Bronchodilator Therapymentioning
confidence: 99%
“…Few investigators have examined the efficacy of bronchodilators in mechanically-ventilated patients [8,11,12,15,[38][39][40][41][42][43][44]. Early studies showed promising results following bronchodilator administration by a MDI [42][43][44], and yet the data were ignored for several years. During that hiatus, adapters to connect a MDI to the ventilator circuit became commercially available.…”
Section: Efficacy Of Bronchodilator Administered By a MDI In Mechanicmentioning
confidence: 99%